Comparative Analysis of Cost of Production Calculation Using Full Costing, Variable Costing, and Target Costing Methods in Determining Product Selling Prices : (Case Study: MSMEs in Gorontalo) - Mohammad Fadel Tosan; Mahdalena Mahdalena; Ikhlas Ul Aqmal (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the comparison of the full cost, variable cost, and target cost methods in calculating the cost of production by MSMEs in Gorontalo, namely Martabak Ar Fachrul, Rolan Upia Karanji, and Taqim Meubel. This study uses a quantitative descriptive approach with primary and secondary data. Data analysis uses the full cost, variable cost, and target cost methods. The results show that each business has its own considerations in choosing the method that best suits its business conditions. Martabak Ar Fachrul and Taqim Meubel chose the full cost method because it covers all production costs, thus providing a more complete cost picture. Meanwhile, Rolan Upia Karanji used the target cost method because the selling price is adjusted to market conditions to remain competitive. The variable cost method was not chosen because it only covers variable costs, so it does not reflect the total production costs and is less appropriate for determining long-term selling prices.